2021
DOI: 10.1021/acs.jpclett.1c02065
|View full text |Cite
|
Sign up to set email alerts
|

From Frequency Domain to Time Transient Methods for Halide Perovskite Solar Cells: The Connections of IMPS, IMVS, TPC, and TPV

Abstract: The correlation of different methods of measurement can become an important tool to identify the dominant physical elements that govern the electronic and ionic dynamics in perovskite solar cells. The diverse phenomena underlying the response of halide perovskite materials to different stimuli are reflected in time-domain measurements, where transients appear with time scales spanning orders of magnitude, from nanoseconds to hours. We discuss the connection between different frequency- and time-domain methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 39 publications
0
63
0
Order By: Relevance
“…The connection between the techniques is explained in ref ; see Figure for the different measurement conditions applied to a simple EC. Impedance Z (ω) is defined in the absence of modulated illumination, Ĵ Φ = 0.…”
Section: Light-modulated Small Perturbation Techniques (Imps and Imvs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The connection between the techniques is explained in ref ; see Figure for the different measurement conditions applied to a simple EC. Impedance Z (ω) is defined in the absence of modulated illumination, Ĵ Φ = 0.…”
Section: Light-modulated Small Perturbation Techniques (Imps and Imvs)mentioning
confidence: 99%
“…Note that the current source and parallel resistance can be transformed to a voltage source and series resistance. Reproduced from ref . Copyright 2020 American Chemical Society.…”
Section: Light-modulated Small Perturbation Techniques (Imps and Imvs)mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 51 ] The charge recombination time increased from 13.3 µs for MA 1.06 PbI 2 Br(SCN) 0.12 based PSCs to 31.3 µs of the MA 0.96 FA 0.1 PbI 2 Br(SCN) 0.12 based champion device (Figure 6c), which further demonstrates the effect of FA + on modifying the perovskite film properties and agrees well the improved FF of the MA 0.96 FA 0.1 PbI 2 Br(SCN) 0.12 based PSCs. Moreover, according to the Laplace transformation, [ 52 ] the carrier recombination lifetime (τ a ) of the R rec C rec circuit in the EIS spectra is calculated to be 54.8 µs and 84.3 µs for the MA 1.06 PbI 2 Br(SCN) 0.12 and MA 0.96 FA 0.1 PbI 2 Br(SCN) 0.12 based PSCs, respectively, which is also consistent with the TPV lifetimes of the corresponding PSCs. [ 53 ] Figure S14 (Supporting Information) shows that the MA 0.96 FA 0.1 PbI 2 Br(SCN) 0.12 based devices also exhibited lower dark current than the MA 1.06 PbI 2 Br(SCN) 0.12 based devices, indicating that the optimized device can more effectively prevent the current leakage, which is in good agreement with the improved J sc and FF of the MA 0.96 FA 0.1 PbI 2 Br(SCN) 0.12 based devices.…”
Section: Resultsmentioning
confidence: 99%
“…To get the insights into the physical processes occurring within the PSC, a unique electrical EC is required, which can represent both the EIS and IMPS plots obtained from the same device. [22] Pockett et al for the first time presented EC for the interpretation of IMPS and IMVS techniques of planar PSCs as the transmission line model used for meso-PSCs earlier [23,24] does not work for planar PSCs. [25] The authors proposed EC, as shown in Figure 1a, consisting of total capacitance (C total ), which represents overall charge stored in the device.…”
Section: Evolution Of Ecmentioning
confidence: 99%